VERMIKULIT ASOSIDA OLINGAN IONITGA MIS (II) KATIONLARINING YUTILISH KINETIKASINING TAHLILI - Tursunmuratov Obid; Bekchanov Davronbek (International Scientific and Current Research Conferences, 2023)
This article presents the results of studying the sorption of copper(II) ions in artificial solutions to the new vermiculite-based ionite at temperatures of 293, 303 and 313 K, the duration of sorption up to the equilibrium state (24 hours) and at different concentrations. Kinetic models of processes (pseudo first and second) were studied. The research shows that the adsorption of Cu(II) ions on vermiculite-based ionite is quenched according to the pseudo-first-order kinetic model, and the correlation coefficient of the pseudo-first-order kinetic model is correspondingly Cu2+ (R2=0.788-0.936), pseudo - the correlation coefficient of the second-order kinetic model Cu2+ (R2=0.682-0.701) was found to be equal. Elemental analysis and SEM images of ionite were obtained. It can be concluded that new ionite absorbed Cu2+ ions through chemical sorption